Preparing democratic early childhood teachers in Don't Say Gay times: how course readings fall short - Cooper, Patricia M.; Casey, Erin M. (Journal of early childhood teacher education, 2023)
Professional literature in human development, social foundations, and academic subject area courses function as a major but understudied tool of teacher preparation programs. Through the overlapping lenses of sociocultural and critical theories of child development, this study employs descriptive content analysis to investigate the potential of common course texts to foster early childhood teachers' proleptical identities as practitioners of democratic education. Findings suggest NAEYC's influential texts on anti-bias education, as well as popular texts in child development, children's literature, and social studies, insufficiently address the democratic goal of fully inclusive classrooms. The presentation of same-sex parent families serves as an exemplar of the problem. Implications for teacher education are discussed.